The Effect of Mathematical Disposition and Learning Style on Learning Motivation and Learning Achievement Online - Isnurani, Isnurani; Mirza, Ade; Martina, Dina (IJBLE Scientific Publications Community Inc., 2025)
A number of characteristics, such as mathematical inclination and motivation to learn mathematics, must be taken into account during the mathematics learning process. The location of the study was SMPN 1 Tajurhalang. 107 students made up the sample for this study, which was selected using a probability sampling technique and data was gathered through questionnaires. The study variables include learning achievement (Y), learning desire (Z), learning style (X2), and mathematical inclination (X1). Path analysis is the type of data analysis used. The study's conclusions are as follows: (1) mathematical style and disposition directly affect online learning motivation; (2) mathematical style and disposition directly affect online learning achievement; (3) mathematical style and disposition indirectly affect online learning motivation; and (4) mathematical style and disposition indirectly affect mathematical disposition through online geometry learning achievement.